2022
DOI: 10.1177/20503121221077834
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ultrasonographic optic nerve sheath diameter to head computed tomography scan to predict intracranial pressure elevation

Abstract: Introduction: Intracranial hypertension is an emergency condition that needs to be recognized as soon as possible. Lumbar puncture, the gold standard diagnostic procedure for intracranial hypertension, is contraindicated in some conditions while brain imaging procedures may be too difficult to be performed on critically ill patients. To solve this problem, this study aims to assess an alternative method to detect intracranial hypertension by measuring optic nerve sheath diameter using ocular ultrasound and opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Moreover, there was non-significant mean coronal ONSD in comparison to mean axial ONSD in both groups. In accordance with our results Sitanaya et al [18] , discovered that groups with raised intracranial pressure had mean optic nerve sheath diameters that were larger than those in the control groups. Similar to our study, Wang et al's [19] findings showed a substantial difference in external ONSD in trauma patients.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, there was non-significant mean coronal ONSD in comparison to mean axial ONSD in both groups. In accordance with our results Sitanaya et al [18] , discovered that groups with raised intracranial pressure had mean optic nerve sheath diameters that were larger than those in the control groups. Similar to our study, Wang et al's [19] findings showed a substantial difference in external ONSD in trauma patients.…”
Section: Discussionsupporting
confidence: 93%
“…Though there is recent evidence suggesting no difference in ONSD when measured between 3 and 5 mm posterior to the globe [ 45 ], most studies base their measurements at 3 mm [ 43 ]. The ONSD is measured between the outer hyperechoic borders of the subarachnoid space ( Figure 3 ) [ 2 , 46 ]. If no hyperechoic stripe is visualized, the diameter is measured at the border of the hypoechoic optic nerve and the hyperechoic retrobulbar fat [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a noninvasive estimation of the intracranial pressure and the detection of increased intracranial pressure can be achieved with the help of ultrasound-guided measurement of the optic nerve sheath diameter (ONSD). A non-invasive method to estimate changes in the ICP in humans is to measure the optical nerve sheath diameter (ONSD) using ultrasound [9][10][11]. Several studies on patients undergoing RALP have shown that the ONSD can increase significantly [12][13][14].…”
Section: Introductionmentioning
confidence: 99%